2017
DOI: 10.1159/000477793
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Effusion in Multiple Myeloma: Characteristics and Practice Patterns

Abstract: In many Asian countries battling with the double burden of increasing noninfectious diseases on top of infectious diseases, multiple myeloma (MM) patients presenting with pleural effusion (PE) pose a great diagnostic challenge. Thus, we aimed to analyze the clinical features and practice patterns of such patients. This is a multicenter retrospective study of newly diagnosed MM patients between January 2011 and December 2015. Among 575 MM patients diagnosed during the study period, 80 (13.9%) that were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Multiple myeloma (MM), a plasma cell cancer, is responsible for 10% of blood malignancies [ 6 ]. Plasma cells cause M protein hypersecretion, a defective immunoglobulin that causes the well-known CRAB syndrome, including hypercalcemia, renal failure, anemia, and bone lytic lesions [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple myeloma (MM), a plasma cell cancer, is responsible for 10% of blood malignancies [ 6 ]. Plasma cells cause M protein hypersecretion, a defective immunoglobulin that causes the well-known CRAB syndrome, including hypercalcemia, renal failure, anemia, and bone lytic lesions [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though these malignant cells are most frequently located in the bone marrow, they can also be found in extramedullary tissues. The thorax is a well-known site for skeletal disease (lytic bone lesion or pathological fracture), plasmacytomas, pulmonary infiltrates (including infections), and pleural effusions, amongst many other findings [ 4 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Given the presence of malignant plasma cells in pleural effusion outside bone marrow, myelomatous pleural effusion (MPE) is considered as a manifestation of EMD, reported in<1% of MM patients. 4 , 5 Byun et al 5 reported MPE accounted for 8.8% in the whole MM patients with pleural effusion, stressing the importance of watching out for MPE when MM patients develop pleural effusion. Besides, some reports described MPE to be associated with an inferior prognosis to MM without extramedullary infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…Pleural effusion (PE) in multiple myeloma is not an uncommon finding, comprising about 6-14% of MM patients (4)(5)(6). The most common causes of MM associated PE are congestive heart failure, renal failure with or without nephrotic syndrome, parapneumonic effusion and amyloidosis.…”
Section: Introductionmentioning
confidence: 99%